Risk Factors for Preterm Labor among Women Attending El Shatby Maternity University Hospital, Alexandria, Egypt - Nermeen Saad El Beltagy; Mohamed Mustafa Rocca; Heba Mahmoud TahaEL-Weshahi; Marwa Samir Abdel Hamid Ali (Archives of Nursing Practice and Care - Peertechz Publications, 2016)
Introduction: Despite the progress made in perinatal medicine over the past two decades, the problem of preterm labor continues to frustrate satisfactory reproductive outcomes and its prevention still awaits needed improvements. Several factors have been identified to be associated with preterm birth (PTB). Objective: To identify the possible epidemiological risk factors contributing to the occurrence of preterm birth among women attending El Shatby Maternity University Hospital. Methods: A case control study was carried out. Two hundred women who delivered preterm babies (from 22 weeks to less than 37 completed weeks of gestation) were matched for BMI with 200 women who  delivered full term babies (equal to or more than 37 completed weeks of gestation). Data were collected using a face to face interview, along with a record review. The variables found to be significantly related to preterm birth by the initial univariate analysis were further analyzed using a multiple logistic regression analysis. Results: Being primigravida, with hypertensive disorders of pregnancy, antepartum hemorrhage, and previous history of preterm birth were found to be associated with a high probability of PTB (OR > 10.5). Past history of gynecological operations and history of urinary tract infection were found to be associated with a moderate probability of PTB (OR>4.5-10.5). Conclusion: Improvement of the current practice of screening for and the treatment of either gynecological or chronic medical disorders that could complicate pregnancies could decrease the risk of preterm birth.